2016
DOI: 10.1080/10245332.2016.1258846
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of outcomes for primary mediastinal large B-cell lymphoma treated with RCHOP followed by radiotherapy or front-line autologous stem cell transplantation

Abstract: The PFS and OS rate of RCHOP/IFRT were found to be unsatisfied. RCHOP/ASCT showed a satisfactory PFS and OS rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The use of CRT remains controversial among hematology centers worldwide; some centers choose to apply it systematically 9,11 or optionally (for metabolic partial responders) CRT [12][13][14] , and other centers no longer employ this approach [15][16][17] . Finally, the place of autologous stem cell transplant (ASCT) in first-line consolidation 18,19 , mainly guided by fluorodeoxyglucose (FDG) positron emission tomography (PET) response assessment 20 , also remains a cause of debate due to the paucity of available evidence in PMBL. Indeed, because PMBL is uncommon, there exist few prospective data, resulting in the present situation of no clearly established standard of care.…”
Section: Introductionmentioning
confidence: 99%
“…The use of CRT remains controversial among hematology centers worldwide; some centers choose to apply it systematically 9,11 or optionally (for metabolic partial responders) CRT [12][13][14] , and other centers no longer employ this approach [15][16][17] . Finally, the place of autologous stem cell transplant (ASCT) in first-line consolidation 18,19 , mainly guided by fluorodeoxyglucose (FDG) positron emission tomography (PET) response assessment 20 , also remains a cause of debate due to the paucity of available evidence in PMBL. Indeed, because PMBL is uncommon, there exist few prospective data, resulting in the present situation of no clearly established standard of care.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation technologies have evolved dramatically over the past decades, challenging the old concepts of RT. However, the role of radiation therapy has been controversial and the results of reported studies are contradictory [7][8][9][10]. So, it is time to rethink the value and necessity of RT in this new era.…”
Section: Introductionmentioning
confidence: 99%
“…Despite dramatic improvements in response rates with the introduction of rituximab (R), R-CHOP was historically administered with consolidative radiation [5]. Given the long-term risks of mediastinal radiation in this predominantly young, female population, including cardiovascular disease and secondary breast cancer, many investigators favored radiation-sparing regimens, such as R-CHOP with time intensification or R-CHOP followed by R-ICE or autologous bone marrow transplant [6][7][8]. A study at the NCI demonstrated 93% event free survival and 97% overall survival at 5 years with a regimen of dose adjusted etoposide, prednisone, vincristine, cyclophosphamide, doxorubicin, and rituximab (DA-R-EPOCH), with no patients receiving consolidative mediastinal radiation.…”
Section: Introductionmentioning
confidence: 99%